2017
DOI: 10.1038/modpathol.2016.205
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid transcription factor-1 distinguishes subependymal giant cell astrocytoma from its mimics and supports its cell origin from the progenitor cells in the medial ganglionic eminence

Abstract: Subependymal giant cell astrocytoma is a benign brain tumor mostly associated with tuberous sclerosis complex. However, it may be misinterpreted as other high-grade brain tumors due to the presence of large tumor cells with conspicuous pleomorphism and occasional atypical features, such as tumor necrosis and endothelial proliferation. In this study, we first investigated thyroid transcription factor-1 (TTF-1) expression in a large series of subependymal giant cell astrocytomas and other histologic and location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…The BRAF V600E mutation was reported in a small set (6 of 14 cases) of SEGAs [ 23 ] suggesting that it could explain MAPK/ERK and AKT activation in SEGAs. However, subsequent studies have produced contradictory results, failing to confirm the presence of the BRAF V600E mutation in SEGAs [ 18 , 21 , 23 , 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation was reported in a small set (6 of 14 cases) of SEGAs [ 23 ] suggesting that it could explain MAPK/ERK and AKT activation in SEGAs. However, subsequent studies have produced contradictory results, failing to confirm the presence of the BRAF V600E mutation in SEGAs [ 18 , 21 , 23 , 26 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…While most of the tumor cells in SEGA display astrocytic features and show patchy immunoreactivity for GFAP, other tumor cells more closely resemble neurons or have intermediate features with astrocytoma‐like cytoplasms and neuronal‐like nuclei; these may show expression for neuronal markers . Recently, some papers suggested that thyroid transcription factor‐1 (TTF‐1) is a good marker that can distinguish SEGA from its mimics and supports its cell origin from the progenitor cells in the medial ganglionic eminence . Although no TTF‐1 was performed in our case, the presence of a cellular CN‐like component with permeative borders and a clinical course of tumor recurrence and absence of tuberous sclerosis make the differential diagnosis of SEGA unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…3G) by cross reactivity of this antibody to dog cells. The CDX-2 antibody, which is used for determining human intestinal NETs [6,10], did not react in the tumor cells. Interestingly, antibody against ACTH detected the tumor cells ( Fig.…”
mentioning
confidence: 92%
“…In dogs and cats, these tumors occur in the intestines, esophagus, lungs, naso-oral cavity and skin [13-16, 18, 23]. In humans, the most common sites are the gastrointestinal and respiratory tracts [2,6,10,22]. Most of these tumors are malignant and aggressive [13,18,20,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation